Humboldt der Seefahrer und sein Marinechronometer Ein Beitrag zur Geschichte der Nautik und Meereskunde - Gerhard Kortum (HiN - Alexander von Humboldt im Netz. Internationale Zeitschrift für Humboldt-Studien, 2001)
Article in German, Abstracts in English, Spanish and German. HUMBOLDT the Navigator and his ChronometerA Contribution to the History of Navigation and OceanographyHUMBOLDT acquired a remarkable precision time-keeper instrument shortly before he left Paris for his Journey to the Neotropics (1799-1804). This chronometer was made by the famous Swiss-French watchmaker Louis BERTHOUD (1753-1813) with the series number 27. It had belonged to "the celebrated BORDA", as HUMBOLDT stated in his "Personal Narrative". Jean Louis BORDA (1733-1799) was a 18th century French navigator, mathematician and cartographer, who invented or improved a number of geomagnetic instruments. HUMBOLDT used this pocket chronometer for his routine astronomic and geomagnetic observations and to fix the longitude of his position while on board a vessel in the Atlantic and Pacific Ocean. Until John "Timekeeper" HARRISON developed his famous "H 4" chronometer in 1773, a strategic invention for a maritime power as Great Britain, the longitude was a major navigational problem. HUMBOLDT, who confessed that he had a "peculiar predelication for the sea", developed great nautical skills, and his findings were much better than those of the pilots. Furthermore he used the chronometer to observe and calculate ocean currents and to improve the geographical coordinates and thus the maps for many places in Latin America. So, beside his thermometer and barometer, the chronometer certainly was a very basic instrument in the state-of-the-art collection of scientific equipment he bought before leaving Europe.